Measles Virus Hemagglutinin: Structural Insights into Cell Entry and Measles Vaccine - Hashiguchi, Takao; Maenaka, Katsumi; Yanagi, Yusuke (Frontiers in Microbiology, 2011)
Measles is one of the most contagious viral diseases, and remains a major cause of childhood morbidity and mortality worldwide. The measles virus (MV), a member of the family Paramyxoviridae, enters cells through a cellular receptor, the signaling lymphocyte activation molecule (SLAM), CD46 or nectin-4. Entry is mediated by two MV envelope glycoproteins, the hemagglutinin (H) and the fusion (F) protein. The H protein mediates receptor attachment, while the F protein causes membrane fusion. The interaction between the H and F proteins is essential to initiate the cell entry process. Recently determined crystal structures of the MV H protein unbound and bound to SLAM or CD46 have provided insights into paramyxovirus entry and the effectiveness of measles vaccine.